Readiness For Learner Autonomy: Bangladeshi EFL Learners’ Motivation, Attitude and Practices - Rajib, Md. Khurshid Hassan; Jahan, Rubaiyat (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This qualitative study underscores the potential variability in learners’ autonomous learning due to the differences in psychological factors, and endeavors to explore Bangladeshi English English language learners’ motivation, attitude, and practices for conceptualizing their readiness for learner autonomy. Methodology: To reach its aim, a qualitative research design was employed to investigate the participants’ motivation, attitudes, and practices. Data were collected through semi-structured interviews with 20 students enrolled in an EFL program in different Bangladeshi universities. Thematic analysis was used to analyze the interview data, relating to the key themes related to learner autonomy. Main Findings: The findings substantiate the participants’ readiness as evidenced by their clear learning goals, active engagement in a wide range of autonomous practices, and positive attitudes towards autonomous learning. However, a significant degree of teacher dependency traced among the participants, leading the study to classify their readiness as ‘reactive autonomy’. Novelty/Originality of this study: This study is unique in a sense that it explores learners’ readiness for autonomy by gauging their motivation, attitude, and practices from a holistic perspective. It bridges gaps in the existing literature by addressing both motivational and attitudinal aspects of the learners, offering nuanced insights into fostering learner autonomy, particularly in contexts like Bangladesh, where traditional, teacher-centered approaches have long dominated the educational landscape.